Direct Visualization and Identification of Membrane Voltage‐Gated Sodium Channels from Human iPSC‐Derived Neurons by Multiple Imaging and Light Enhanced Spectroscopy (Small Methods 7/2022). Issue 7 (20th July 2022) - Moretti, Manola; Limongi, Tania; Testi, Claudia; Milanetti, Edoardo; De Angelis, Maria Teresa; Parrotta, Elvira I.; Scalise, Stefania; Santamaria, Gianluca; Allione, Marco; Lopatin, Sergei; Torre, Bruno; Zhang, Peng; et al.
Abstract : Direct Visualization In article number 2200402, Moretti, Di Fabrizio, and co‐workers developed a method to directly image and characterize ion channels in their native cell membrane environment by transmission electron microscopy, atomic force microscopy, and enhanced Raman spectroscopy.